CORRELATION BETWEEN SOCIAL ATTITUDES AND SOCIAL SCIENCES LEARNING OUTCOMES TO FOURTH GRADE STUDENTS OF PUBLIC ELEMENTARY SCHOOLS IN KEBUMEN SUB-DISTRICT IN ACADEMIC YEAR OF 2019/2020 - Sandhi, Dwi Pungky Ari; Suhartono, Suhartono; Joharman, Joharman (Kalam Cendekia: Jurnal Ilmiah Kependidikan, 2020)
The implementation of social attitudes in the 2013 curriculum is part of character education having positive impact on academic achievement. The study aimed to prove positive correlation between social attitudes and social sciences learning outcomes and to determine the contribution of social attitudes toward social sciences learning outcomes to fourth grade students of public elementary schools in Kebumen Sub-district in academic year of 2019/2020. The study used a quantitative research design with correlation method. Sampling method was cluster random sampling technique. The result showed that there was positive relationship between social attitudes and social sciences learning outcomes of fourth grade students with low correlation level which was 0.117. The adjusted R square value of social attitudes to social sciences learning outcomes was 1.38%. It concludes that there is a positive correlation between social attitudes and social sciences learning outcomes to fourth grade students of SDN in Kebumen Sub-district in academic year of 2019/2020.